Population trends of the sugarcane leaf hopper Pyrilla perpusilla (Walker) (Homoptera: Lophopidae) and its parasitoids in relation to weather factors in the Tarai region of Uttarakhand, India - Saba Tanveer; R. P. Maurya (Egyptian Journal of Biological Pest Control)
Abstract Background Pyrilla perpusilla (Walker) is an important pest of sugarcane ecosystem in the Tarai region of Uttarakhand state of India. The study focused on investigating the population dynamics of Pyrilla (sugarcane leaf hopper) and its parasitoids under the natural field conditions. Results During the study, two important parasitoids, viz., Fulgoraecia Melanoleuca, a nymphal/adult parasitoid (Lepidoptera: Epipyropidae), and Cheiloneurus pyrillae, an egg parasitoid (Hymenoptera: Encyrtidae), were found associated with the sugarcane leaf hopper. The peak mean population of ecto-parasitoid, F. melanoleuca cocoon, was observed in November 2022–23 and 2023–24. The morning hour relative humidity showed a negative significant relation with the cocoon population. The maximum parasitization of nymphs and adults Pyrilla was found to be 46.7 and 46.0%, respectively, from September to October during 2022–23 and 2023–24 crop seasons, after that the declining trend in parasitization by F. melanoleuca was observed. An increasing trend was recorded in egg parasitization in July, when the maximum mean population density of Pyrilla egg batches (2.28 /leaf), nymphs (4.75/leaf) and adults (4.58/leaf) was found. Temperature and relative humidity had significant correlations with Pyrilla egg batches. Conclusion Overall, the study outlines the presence of Pyrilla and its naturally occurring parasitoids in the sugarcane ecosystem, along with the effects of weather conditions on Pyrilla’s population density and the parasitization rates of the parasitoids. The peak activity period of pest and its parasitoids was reported from September to November. Weather factors such as temperature ranging from 16 to 37.25 °C and relative humidity (62.7–93.8%) played a significant role in affecting their density and parasitization.